An interview study of how clinical teachers develop skills to attend to different level learners. (2nd June 2016) - Chen, H. Carrie; Fogh, Shannon; Kobashi, Brent; Teherani, Arianne; ten Cate, Olle; O'Sullivan, Patricia
Abstract: Purpose: One clinical teaching challenge is the engagement of learners at different levels. Faculty development offerings mostly address general strategies applicable to all learners. This study examined how clinical faculty members develop the skills to work with different level learners. Methods: We conducted semi-structured interviews with medical school faculty members identified as excellent clinical teachers teaching multiple levels of learners. They discussed how they developed their approach to teaching different level learners and how their teaching evolved over time. We performed thematic analysis of the interview transcripts using open and axial coding. Results: We interviewed 19 faculty members and identified three themes related to development of teaching practices: teacher agency and work-based learning of teaching strategies, developmental trajectory of clinical teachers, and interplay between clinical confidence and teaching skills. Faculty members were proactive in using on-the-job experiences to develop their teaching practices. Their teaching practices followed a developmental trajectory towards learner centeredness, and this evolution was associated with the development of clinical skills and confidence. Conclusions: Learning skills to teach multi-level learners requires workplace learning. Faculty development should include workplace learning opportunities and use a developmental approach that accounts for the trajectory of teaching as well as clinical skills attainment.